Synthesis, Crystal Structure, Thermal Decomposition, and B-11 MAS NMR Characterization of Mg(BH4)(2)(NH3BH3)(2) - Jepsen, Lars H.; Ban, Voraksmy; Moller, Kasper T.; Lee, Young-Su; Cho, Young Whan; Besenbacher, Flemming; Filinchuk, Yaroslav; Skibsted, Jorgen; Jensen, Torben R. (American Chemical Society, 2014)
A metal borohydride ammonia borane complex, Mg(BH4)(2)(NH3BH3)(2) was synthesized via a solid-state reaction between Mg(BH4)(2) and NH3BH3. Different mechanochemical reaction mechanisms are observed, since Mg(BH4)(2)(NH3BH3)(2) is obtained from alpha-Mg(BH4)(2), whereas a mixture of Mg(BH4)(2)(NH3BH3)(2), NH3BH3, and amorphous Mg(BH4)(2) is obtained from gamma-Mg(BH4)(2). The crystal structure of Mg(BH4)(2)(NH3BH3)(2) has been determined by powder Xray diffraction and optimized by first-principles calculations. The borohydride groups act as terminal ligands, and molecular complexes are linked via strong dihydrogen bonds (<2.0 angstrom), which may contribute to the high melting point of Mg(BH4)(2)(NH3BH3)(2) found to be similar to 48 degrees C in contrast to those for other molecular metal borohydrides. Precise values for the B-11 quadrupole coupling parameters and isotropic chemical shifts are reported for the two NH3BH3 sites and two BH4- sites in Mg(BH4)(2)(NH3BH3)(2) from B-11 MAS NMR spectra of the central and satellite transitions and MQMAS NMR. The B-11 quadrupole coupling parameters agree excellently with the electric field gradients for the B-11 sites from the DFT calculations and suggest that a more detailed structural model is obtained by DFT optimization, which allows evaluation of the dihydrogen bonding scheme.
Keywords: HYDROGEN STORAGE PROPERTIES; NUCLEAR-QUADRUPOLE MOMENTS; AMMONIA-BORANE; MAGNESIUM BOROHYDRIDE; LITHIUM; AMIDOBORANE; MG(BH4)(2); STABILITY; CHEMISTRY; HYDRIDES